Empowered Educators in Canada: How High-Performing Systems Shape Teaching Quality - Campbell, Carol; Zeichner, Ken; Lieberman, Ann; Osmond-Johnson, Pamela (Jossey-Bass, 2017)
BEST PRACTICES FROM CANADA'S HIGH-PERFORMING SCHOOL SYSTEMS Empowered Educators in Canada is one volume in a series that explores how high-performing educational systems from around the world achieve strong results. The anchor book, Empowered Educators: How High-Performing Systems Shape Teaching Quality Around the World, is written by Linda Darling-Hammond and colleagues, with contributions from the authors of this volume. Empowered Educators in Canada details the core commonalities that exist across Canada with special emphasis on the localized nature of the systems—a hallmark of Canadian education. Canada boasts a highly educated population, and the provinces/territories truly value education as evidenced by the significant proportion of public funds allocated to schooling. Operated by the provinces and territories, participation in kindergarten, primary, and secondary education is close to 100% across the nation. In addition to offering traditional academics, secondary education includes opportunities for students to attend technical and vocational programs. To demonstrate exemplary education systems, the authors examine two top-performing jurisdictions, Alberta and Ontario, which have developed strong supports for teacher development. Canadian teachers are highly qualified, and salary scales in all jurisdictions are typically based on a teacher's level of education and years of experience. While Canada has enjoyed much educational success, the education of First Nations students has historically been one of the country's more controversial and contentious issues. Overall, Canada is a country that is proud of its education system and places a high value on—and participation in—publicly funded education.